Advances in solid catalysts for selective hydrogenolysis of glycerol to 1,3-propanediol - Bhowmik, Susmita; Darbha, Srinivas (Catalysis Reviews-Science and Engineering, 2021)
Glycerol is one of the top 12 platform chemicals obtained from biomass. Its surplus availability as a by-product of biodiesel, fat-splitting and soap manufacturing industries and affordable price lends significant opportunity for its valorization, using solid catalysts, into propanediols (PDOs), particularly to 1,3-propanediol (1,3-PDO), by selective hydrogenolysis. 1,3-PDO is an important chemical with wide applications including that as a precursor in polymers manufacturing. However, the synthesis of 1,3-PDO by selective cleavage of the secondary C-O bond of glycerol in the presence of hydrogen (instead of the primary C-O bond yielding 1,2-PDO) is highly challenging. Of late, supported Pt and Ir catalysts in combination with a reducible oxide (WO(x)or ReOx) were found selective for 1,3-PDO formation. Support, metals composition and additives (co-added metals) affect the performance of these catalysts. Detailed investigations revealed that metal dispersion, electronic connectivity between metal and metal oxide/support, hydrogen activation/spillover and Bronsted acidity are some parameters that influence the activity and selectivity of these bi-functional, metal-metal oxide catalysts. This review summarizes the latest advances in these solid catalysts for selective hydrogenolysis of glycerol to 1,3-PDO, a monomer for advanced polymers.
Keywords: 1; 3-Propanediol; bifunctional metal-metal oxide catalyst; biomass valorization; Glycerol; Hydrogenolysis